Hyperfine study of Cu3(ZrF 7)2·16H 2 O and its thermal decomposition - Ceolín, Marcelo Raúl (1994)
By use of the time differential perturbed angular correlations technique, the hyperfine interactions at zirconium sites in Cu2(ZrF7)2·16H2O and its decomposition products were determined between 300 and 700 K. A simple model to give account of the decomposition process is presented in agreement with angular correlation and gravimetric results.